HUBUNGAN BAHASA DAN PIKIRAN DALAM JUAL-BELI DI GRUP FACEBOOK BUSAM TINJAUAN PSIKOLINGUISTIK - Wahyuni, Desna Try; Mulawarman, Widyatmike Gede; Purwanti, Purwanti (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This study links language, mind and Facebook social media. Currently, buying an selling using social media is a common thing to do by the community, but it should be noted that: 1) Language and thought relations in every sale and purchase transaction on the BUSAM Facebook group. This study uses the theory of Sapir-whrof, Jaen Piaget, and also Vygotsky, using psycholinguistic studies. This research use descriptive qualitative approach. Data is obtained by using a screen capture (screenshot) status in the BUSAM Facebook group. In addition, users also use the Facebook account interview technique. Then, examine and record the data obtained for analysis in accordance with predetermined theories. The results of this study state that, language and thought used by the community are generally an interrelated activity. So that the two cannot be separated. Language can influence the mind using sentences expressed through oral and written. The mind can influence language with ideas that arise in the mind and language as an intermediary for its expression. Language and mind, of course, cannot be separated because the two are interconnected and have an important role for society.